Managing Tourist's Perception of Safety and Security while Visiting Antigua - Nathaniel-Skerritt, Patrice (2009)
This study examines the issue of safety and security from the perspective of accommodation providers and from that of the consumer, tourists. As part of the background analysis, the study begins by defining the keys terms of the research, tourism, perceptions, safety and security. It then goes on to analyze trends in the tourism industry from the global, regional and national level. In this regard, it shows that tourism is one of the largest and fastest growing industries in the world. It also shows the importance of the industry to the economy of Antigua. The study also identifies the main safety and security threats to tourism as, crime, natural disasters and political instability and terrorism. The research then discusses each of the threats to the tourism industry in an effort to highlight the negative impacts that they have had on the industry. While these are exogenous factors to the tourism industry, their occurrence at a tourist destination can negatively impact the industry if they are perceived as threats to the safety and security of visitors. These in turn act as push factors for visitors away from the destination where potential visitors will then seek out other destinations that are perceived to be safer. Therefore in light of these threats the question arises as to whether visitors to Antigua perceive the destination as a safe place to visit? And, are there adequate safety and security measures in place at accommodation facilities to keep guests safe? The answers to these questions are gathered from data provided in the 2008 Accommodation Safety and Security Audit and an exit survey of visitors to Antigua. Both of these studies should reflect on each other, in that, if safety and security measures are in place at the hotels where most visitors stay, this should reflect in a positive perception and vice versa. The findings of the study show that visitors to Antigua perceive the island as safe place to visit. It also shows that most accommodation facilities provide basic safety and security measures for guests. The study ends by giving recommendations on how to continue to further improve and maintain the positive perceptions of safety and security that visitors have of the destination.